Gricean Maxim Violations in a Javanese Song Entitled Slénco - Yulius Nahak; Barli Bram (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Conversation, as a complex activity, requires some set of rules to be guided and worked cooperatively. However, violating the rules to create implications in some situations is a powerful and creative way to get across a point. This study attempts to discover the most dominant maxim violation in a Javanese song entitled Slénco by applying a qualitative approach. The data source is taken from the Internet in the form of dialogue manifested via musical communication, which violated Cooperative Principles of Maxims. To conduct this study, three steps were taken: Copying the song lyrics and translating them into English; categorizing them into different types of maxims violation; analysing them based on the violation of each maxim; and then concluded the reasons why the lyricists violated the Cooperative Principle of maxims in their utterances. The findings of the study showed that all types of maxims were violated: eight utterances on the maxim of quantity, three utterances on the maxim of quality, 11 utterances on the maxim of relations, and eight utterances on the maxim of manners. These violations of maxims portray the reality of dyslexia sufferers who are problematic in conversational exchanges and make the lyrics sound funny as a form of art in indirect communications.